Principal Strategies in Strengthening School-Based Management to Improve Madrasah Quality - Jufri (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This study examines the principal’s strategies in strengthening School-Based Management (SBM) to improve madrasah quality at MAN 1 Baubau. The research is positioned within contemporary educational governance debates that emphasize decentralization, accountability, and continuous quality improvement in school organizations. Using a qualitative case study approach, the study focuses on how leadership practices translate SBM principles into operational programs and routines, and how these practices shape instructional quality and organizational capacity. Data were generated through semi-structured interviews with key stakeholders (madrasah principal, vice principals, teachers, administrative staff, and committee representatives), direct observations of managerial and instructional routines, and document analysis of planning and evaluation records. Data analysis followed an interactive model involving data reduction, data display, and conclusion drawing, supported by triangulation and member checking to enhance trustworthiness. The findings indicate that SBM strengthening is pursued through: (1) strategic alignment of the vision–mission with measurable annual targets and prioritized quality programs; (2) participatory governance structures that distribute roles and responsibilities through functional teams and routine coordination forums; (3) evidence-informed planning and managerial control through monitoring, evaluation, and follow-up mechanisms consistent with continuous improvement logic; (4) instructional leadership practices, including formative academic supervision and teacher professional learning activities; and (5) resource governance and student service strengthening to improve process reliability and learning conditions. Persistent challenges include uneven staff engagement, administrative workload pressures, and limited digital integration of data systems that affect responsiveness. Overall, the study suggests that SBM can operate as a sustainable quality improvement mechanism when leadership integrates direction (targets), systems (routines), and people (capacity and culture), thereby moving implementation beyond document compliance toward measurable improvements in madrasah quality.